Report of Energy Audit in Building F1, F3, F4, and G6 of Universitas Muhammadiyah Yogyakarta - Destria Yoga Ningrum; Anna Nur Nazilah Chamim; Ramadoni Syahputra; Jamaaluddin Jamaaluddin (Journal of Electrical Technology UMY, 2019)
Energy audits on buildings are carried out to determine the load profile of electrical energy usage and to avoid wasting electricity. This energy waste can cause the use of electricity in buildings that are not efficient. An electrical energy audit is carried out to produce actual data that is in accordance with existing building conditions. This study conducted on buildings F1, F3, F4, and G6 in Universitas Muhammadiyah Yogyakarta to determine the value of the intensity of energy consumption used, whether it is following the Indonesian National Standards Agency. Measurement of electrical energy consumption using a tool that is the Power Factor Analyzer. The results of the calculation of the value of the intensity of electrical energy consumption showed that the buildings of F1, F3, F4, and G6 at the Universitas Muhammadiyah Yogyakarta obtained an average energy intensity value of 10.18 kWh/month. In this case, building standards are known to be between 7.92 - 12.08, which means that the building standards are categorized as efficient because they are under established standards. Furthermore, the use of electrical energy consumption used in buildings F1, F3, F4, and G6 in Universitas Muhammadiyah Yogyakarta in a month that is equal to 190,952.769 kWh/month.